Pelatihan Pijat Oksitosin kepada Keluarga untuk Meningkatkan Produksi ASI pada Ibu Menyusui - Asmin, Risna Yunita; Rahmat, Rezqiqah Aulia; Pratiwi, Desi Eka (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Breast milk production is significantly influenced by hormonal and psychological factors, one of which is stimulation of the hormone oxytocin. Oxytocin massage is a simple technique that can be performed by family members to stimulate breast milk production. This community service program aims to provide oxytocin massage training to families of breastfeeding mothers as a promotional intervention to increase breast milk production. The activity was implemented through counseling, demonstrations, hands-on practice, and follow-up mentoring for 25 families in Sukamaju Village. Evaluation results showed an increase in family knowledge and skills in performing oxytocin massage, as well as a positive impact on breast milk flow. This training has proven effective and can be recommended as a routine program in pregnancy and breastfeeding classes at the community level.